Communicative Approach, Task-based Approach and the Development of Competences in Foreign Languages - Edmundo Calvache (Asociación Colombiana de Profesores de Ingles, 2017)
The communicative approach has been around for more than a quarter of a century. However, its implementation in places like our country has not always been an easy task due, partly, to disinformation. The goal of this article is to provide teachers with a concise review of the concepts of communicative competence, task-based instruction (TBI), and competence. We also intend to provide some insights about teacher roles and task creation in TBI.